Learning situations: Analysis, d Learning situations: Analysis, development and supervision - Prieto Román, Alberto José (Avances en Supervisión Educativa, 2024)
The analysis of learning situations is approached from the perspective of different educational administrations and authors. After this analysis, alternatives for the development of these situations are offered, as an element of curricular and didactic concretion/decision, going in depth into each of its elements. At the same time, a general theoretical and didactic approach is made and it ends by offering different supervision models to be used by the educational inspection which, at the same time, can be used as advice for teachers.